banner
home icon
 

 

Function Notation and How to Evaluate a Function

 

The common notation of a function is usually written as,

f(x).

Don't think of this too literally, that is, "f" is being multiplied to "x". Instead, consider this as a mathematical expression which is read as

 

f is a function x
or
f is some expression involving the variable x

 

Functions can also be written in different ways using other variables such as

  • g(x), h(x), and k(x)

 

In addition, functions may take other input values other than "x".

  • f(a), h(r), and k(m)

 

tip  The key idea is to always remember that the variable outside the parenthesis is the "name" of the function, while the variable inside the parenthesis is the input value of the function.

For instance, the following is called function k with an input value of m.

 

in the expression k(m), the function has a name of "k" and an input value of "m"

 


Example 1: Evaluate the function f(x)=3x-5 when x=-1.

This is the normal notation of function where the function is "f" while the input value is "x". To evaluate a function, what we want is to substitute every instance of "x"in the expression and then simplify.

Since x=-1, we substitute this value in the function and simplify. In doing so, we get a solution that looks like this.

 

f(x)=3x-5, f(-1)=3(-1)-5, f(-1)=-8

 


 

Example 2: Evaluate the function h(k)=2k^2-5k+1 when k=3.

Observe that the function here is "h" and the input value is "k". Just like in our previous example, we want to substitute whatever the numerical value assigned to "k" into the given function, and simplify.

Since k=3, your solution should look similar to this

 

h(k) =2k^2-5k+1, h(3)=2(3)^2-5(3)+1, h(3)=4

 


 

Example 3: Evaluate each value of "x" in the table below using the function f(x)=x^2+2x-3. Plot the points in the xy-axis and connect the dots to reveal the graph of the function.

table of values when x are -4, -3,-2,-1,0,1,2

Since there are seven x-inputs, that means we will evaluate the function seven times as well. Try working this out on your own then come back to check your answers.

If you have done it correctly, these are the values:

f(-4)=5, f(-3)=0, f(-2)=-3, f(-1)=-4, f(0)=-3, f(1)=0, f(2)=5

We can now place those output values in the table.

table of values when the x-values are evaluated using the function  f(x)=x^2+2x-3

Think of the output values of the function f(x) as the y-values. This is how the graph looks like on the xy-axis.

graph of the function f(x)=x^2+2x-3 in the xy-axis

 

Example 4: Given that g(x)=x^2-3x+1 , find g(2x-1).

In previous examples, we have have been evaluating a function by a number. This time the input value is no longer a fixed numerical value, but instead an expression. It might look complicated but the procedure remains the same.

We will replace every instance of "x" in g(x) by the input value which is 2x-1. Simplify by squaring the binomial, applying the distributive property and combining like terms.

g(x)=x^2-3x+1, g(2x-1)=4x^2-10x+5

 


 

Example 5: Given that p(x)=(4x-1)/x, find p(1)-p(-1).

The problem may look intimidating at first, but once we analyze it and apply what we already know on how to evaluate functions, this shouldn't be that bad!

What we need to do here is to evaluate function at x = 1 then subtract by the value of the function when evaluated at x = −1.

Be very careful when you substitute the values and during the simplification process. If you are not careful in every step, it is very easy to commit mistakes when you add, subtract, multiply, or divide positive and negative numbers.

p(1)-p(-1)=-2

 

 


 

Example 6:  If f(2)=9, find the value of "a" in the function f(x)=6x^2+ax-7.

In the equation, f(2)=9, we are told that if the input of the function is "2"; the output of the function will be "9". Since the function is given to us, our first move is to at least substitute the value of "2" and then simplify. This is what we'll get.

f(x)=6x^2+ax-7, f(2)=17+2a

The output of the function after evaluating at x = 2 is 17+2a. Remember, we are also told that the output is 9 using the given equation f(2)=9. Therefore what we need to do now is set them equal to each other, and solve the linear equation for the unknown value of "a".

17+2a=9, a=-4

Let's verify if the value of a=-4 in f(x)=6x^2+ax-7 can make the given condition f(2)=9 to be a true statement.

f(x)=6x^2-4x-7, f(2)=9

It's true! Hence, we have successfully solved for the correct value of "a".

 


 

Practice Problems with Answers
Worksheet 1 Worksheet 2

 

Top of Page
 
JUMP TO:
Algebra Lessons
Algebra Lessons (A-Z)
Algebra Worksheets
Free Math Solver
 
 

 

Liquid Web Managed Word Press 

 

 

 

HOME   |   PRIVACY POLICY   |   CONTACT US   |   DONATE

Copyright 2011-2017   ChiliMath  All Rights Reserved

Powered by Liquid Web